Electronic structure of the double perovskite Ba2Er(Nb,Sb)O 6 - Gil Rebaza, Arles Víctor (2014)
In this work, we present a detailed study of the structural and the electronic structure of the double perovskite Ba2Er(Nb,Sb)O 6. All calculations were performed with the Full-Potential Linear Augmented Plane Wave method (FP-LAPW) based on the Density Functional Theory (DFT). From the minimization of energy as a function of volume using the Murnaghan's state equation has been obtained the equilibrium lattice parameter and the bulk modulus of these compounds. The study of the electronic structure was based in the analysis of the electronic density of states (DOS), and the density of charge, showing that these compounds have a total magnetic moment of 3.0 μB per formula unit due to Er atoms.